Analisis Faktor Yang Berhubungan dengan Kesiapsiagaan Pemuda dalam Menghadapi Bencana Gempabumi - Rahil, Nazwar Hamdani; Amestiasih, Tia (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2021)
Indonesia is located at the junction of four tectonic plates, namely the Asian Continent plate, the Australian Continent, the Indian Ocean plate, and the Pacific Ocean plate. This condition also makes Indonesia prone to earthquakes. The earthquake has an impact on causing loss of life and material. To reduce the impact of disasters, it requires a preparedness to face earthquakes. The purpose of this research is to analyze the factors related to earthquake preparedness. The design of this research is an analytic observation with a cross-sectional approach. The population of this study was members of the Karangtaruna village of Trimulyo, Jetis, Bantul, Yogyakarta, with a total of 200 respondents. The sample size is 122 respondents who are calculated using the Slovin formula, with a simple random sampling technique. The factors analyzed include respondent characteristics (age, gender, education level, marital status, occupation), disaster experience, availability of resources (disaster preparedness team, early warning, evacuation routes), disaster education, frequency of disaster education. The research was carried out from May-September 2020. The results of the study obtained the age of the majority of respondents in the adult category (86.1%), the majority of gender was female (51.5%), the majority of high school education level (65.6%), the majority of students' occupation (43.4%). The majority of respondents had attended disaster education (67.2%), the majority had experienced disaster once (50%), the majority had attended disaster education 1 time (53.3%). Major evacuation routes are in the existing category (73%), and the availability of the disaster preparedness team is mostly in the existing category (50%). The statistical test results obtained KMO and Bartlett's test values (0,000). The results of the factor analysis show that there are two factors that can represent other variables that affect preparedness. These factors are knowledge - attitudes and the availability of infrastructure